IDEOLOGICAL BASES OF THE ISLAMIC GOVERNANCE IN IRAN: TO THE HISTORY OF THE QUESTION - Dzhalilov Z.; Batyrkhan B. (Academic Journal of Physical and Chemical Sciences, 2020)
The issue of the concept of “Islamic republic” continues to be discussed in different countries by orientalists, philosophers, political scientists, lawyers, theologians. At the same time, many researchers pay special attention to the peculiarities of socio-political life, the nature of socio-economic transformations and other phenomena in the Islamic Republic of Iran (IRI) [1, p. 84]. In this, the authors believe that one can come to the right position with respect to the role of clergy in the Iranian revolution, recognizing both the peculiarities of the ideological foundations of Islam and revealing the clergy as a special group of people with their own specific ideals and organizational structure. It defines the content of the Islamic-republican form of government and offers its own vision of the theocratic regime in this country.